Ragamala Phenomenon and Problems of Its Interpretation: The Case of the First Known Images of Ragas - Babin, Alexander N. (Actual Problems of Theory and History of Art, 2019)
This paper examines ragamala, a unique phenomenon of Indian art that connects music, poetry and painting. For more than a century studying, many its aspects have not been investigated sufficiently yet. Although some samples of its first known manifestation in painting became textbook examples for the ragamala studies, the scope of their appearance usually remains out of the researchers’ attention. Notably, those scopes are quite different from those which gave life to the next tradition, and their study clarifies a complex nature of the phenomenon as a whole. The earliest known images of ragas appear in the margins of Kalpasutra, the canonical text of Jainism. Despite their peripheral position in the manuscript, they are presented asan organized system, parallel to the main text, and therefore play a certain role in it. The following study discusses the circumstances that influenced the form and the fact of the appearance of ragas in Kalpasutra manuscript. It also considers the sources of their iconography, and offers an interpretation of their images, based on a comparative analysis with typologically similar objects in Western Indian painting of the same period.